學校教育品質研究發展與現況之文獻計量分析 - 李康莊(Kang Chuang Lee); 吳政達(Cheng-Ta Wu) (Journal of Education Research (Print), 2020)
Countries around the world are now trying to improve the educational quality of schools to enhance the competitiveness of talented people worldwide. Therefore, improving educational quality has been a key issue in education reform. Educational quality of schools means that schools have a good overall performance in resource inputs, operation processes and implementation outputs, and keep improving to meet people’s needs and expectations. In this paper, 1995 literatures on education quality of schools from 1969 to 2019 were retrieved from the Web of Science Core Collection database. The study used visual softwares of bibliometrics to conduct high-cited literature analysis, literature co-citation analysis, and keyword co-occurrence analysis to explore the knowledge base, research hotspots, and research frontiers in the field of educational quality of schools. After bibliometric analysis, the issues of educational achievement, school choice, educational policy and higher education are research hotspots of educat